Serum hepatitis B virus RNA levels as an early predictor of hepatitis B envelope antigen seroconversion during treatment with polymerase inhibitors. Issue 1 (25th November 2014) - van Bömmel, Florian; Bartens, Anne; Mysickova, Alena; Hofmann, Jörg; Krüger, Detlev H.; Berg, Thomas; Edelmann, Anke
<x xml:space="preserve">Abstract</x> Hepatitis B envelope antigen (HBeAg) seroconversion represents an endpoint of treatment of chronic hepatitis B virus (HBV) infections. We have studied whether levels of serum HBV RNA during polymerase inhibitor treatment might be helpful for predicting HBeAg seroconversion. HBV RNA levels were determined in serial serum samples from 62 patients with chronic HBV infection (50 HBeAg positive). Patients received antiviral treatment for a mean duration of 30 ± 15 (range, 4‐64) months. A new rapid amplification of complimentary DNA‐ends‐based real‐time polymerase chain reaction was established for quantitative analysis of polyadenylated full‐length (fl) and truncated (tr) HBV RNA. HBV RNA, HBV DNA, and hepatitis B surface antigen (HBsAg) levels as well as presence of HBeAg and hepatitis B envelope antibody were measured at baseline, month 3, month 6, and subsequent time points. Fifteen patients who achieved HBeAg seroconversion after a mean duration of 19 ± 14 (range, 3‐56) months of antiviral treatment showed a significantly stronger decline in mean HBV flRNA and trRNA levels from baseline to month 3 of 1.0 ± 1.4 (range, −1.6‐3.4) and 2.1 ± 1.4 (range, 0‐3.9) and to month 6 of 1.8 ± 1.4 (range, 0‐4.6) and 3.1 ± 1.7 (range, 0‐5.1) log10 copies/mL, respectively, in comparison to 35 HBeAg‐positive patients without HBeAg seroconversion (P < 0.001 for months 3 and 6). A similar decline in HBV RNA levels was observed in HBeAg‐negative patients. The decline of HBV RNA levels at months 3 and 6 of treatment was to be the strongest predictor of HBeAg seroconversion, when compared to levels of HBV DNA, HBsAg, alanine aminotransferase, and HBV genotype, age, and sex. Conclusion: Serum HBV RNA levels may serve as a novel tool for prediction of serological response during polymerase inhibitor treatment in HBeAg‐positive patients. (Hepatology 2015;61:66–76)